The Effectiveness of Interactive Android Modules through the Culturally Responsive Teaching (CRT) Approach Integrated with Differentiated Learning to Improve the Learning Outcomes of Junior High School Science Independent Curriculum Students - Yurnetti; Khairil Arif; Harmedi Yulian Saputra; Tifani Aisya Djuazva (Postgraduate, University of Mataram, 2025)
This research aims to analyze and explain the validity, practicality, and the effectiveness of interactive android modules through the CRT approach integrated with differentiated learning. Interactive android modules are designed to improve students' understanding so as to improve student learning outcomes. This type of research is research and development (R&D) using the ADDIE design which consists of five stages, namely analysis, design, development, implementation, and evaluation. Results obtained from this research that the validity of the interactive Android module is declared valid in terms of content eligibility, linguistic aspects and aspects of presentation and graphics. Practicality of interactive android module of teacher and student responses is stated for be very practical. The effectiveness of the interactive android module is stated it is quite effective in improving learning outcomes. Based on these findings research, it was concluded that the interactive android module was declared valid with an average score of 0.89. Practicality, it is stated to be very practical Based on the response of teachers with an average score of 0.95 and students response with a score of 0.91. The effectiveness of using the N-Gain test of 0.68 was stated to be medium to be used in improving learning outcomes.